Deconstructing the eradication of new world screwworm in North America: retrospective analysis and climate warming effects. Issue 2 (13th February 2019) - Gutierrez, A. P.; Ponti, L.; Arias, P. A.
Abstract: Before its eradication from North America, the subtropical‐tropical new world screwworm fly Cochliomyia hominivorax (Coquerel) invaded southwestern temperate areas of the U.S.A., where it caused myiasis in wildlife and livestock. Outbreaks of the fly occurred during years when adult migrants were carried northward on North American monsoon winds from the northern areas of Mexico and south Texas. We deconstruct, retrospectively, the biology and the effect of weather on the eradication of the fly in North America. Screwworm was found to be an ideal candidate for eradication using the sterile insect technique (SIT) because females mate only once, whereas males are polygynous, and, although it has a high reproductive potential, field population growth rates are low in tropical areas. In northern areas, eradication was enhanced by cool‐cold weather, whereas eradication in tropical Mexico and Central America is explained by the SIT. Despite low average efficacy of SIT releases (approximately 1.7%), the added pressure of massive SIT releases reduced intrinsically low fly populations, leading to mate‐limited extinction. Non‐autochthonous cases of myiasis occur in North America and, if the fly reestablishes, climate warming by 2045–2055 will expand the area of favourability and increase the frequency and severity of outbreaks. Abstract : Deconstruction of the invasion biology of new world screwworm explains the role of North American monsoons with respect to its dynamics and eradication using the sterile insect technique (SIT). SIT programme myiasis data explained the time lagged effects of weather on observed and potential myiasis outbreaks in Texas. A demographic model explained the fly dynamics in tropical regions. The efficacy of sterile fly releases was assessed and the effects of climate change on the potential expansion of the fly's geographical range in North America were estimated.